1989
DOI: 10.3168/jds.s0022-0302(89)79297-3
|View full text |Cite
|
Sign up to set email alerts
|

Production Responses of Dairy Cows Fed Various Amounts of Rumen-Protected Methionine and Lysine

Abstract: A 3 x 3 factorial response surface design was used to study the effects of feeding rumen-protected methionine and lysine to dairy cows between 22 and 305 d of lactation. A total of 130 dairy cows at three universities were individually fed a corn silage and corn grain-based diet that contained either soybean meal or corn gluten meal and urea. An unsupplemented control diet plus nine treatment combinations of three amounts of rumen-protected DL-methionine (3.4, 7.8, and 12.2 g/d) and three amounts of rumen-prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 21 publications
2
17
0
3
Order By: Relevance
“…The large demand of the mammary gland for amino acids for dairy cows producing in excess of 30 kg a day is well established (Rogers et al 1989). Over 92% of the nitrogenous components in cow's milk are proteins synthesized de nouo in the mammary gland (Clark et a1 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The large demand of the mammary gland for amino acids for dairy cows producing in excess of 30 kg a day is well established (Rogers et al 1989). Over 92% of the nitrogenous components in cow's milk are proteins synthesized de nouo in the mammary gland (Clark et a1 1978).…”
Section: Introductionmentioning
confidence: 99%
“…As formas mais usadas para suprimento pós-ruminal de aminoácidos limitantes são infusão abomasal de proteínas (DERRIG et al, 1974;CLARK et al, 1977e ROGERS et al, 1984 e de aminoácidos protegidos da degradação ruminal (PAPAS et al, 1984;POLAN et al, 1991;ROGERS et al, 1987;ROGERS et al, 1989).…”
Section: Rev Bras Zootec 30(1):286-294 2001unclassified
“…Contrariamente aos resultados obtidos neste estudo, CASPER et al (1987), ROGERS et al (1989); ARMENTANO et al (1993), RULQUIN e DELABY (1994), PIEPENBRINK et al (1996), PISULEWSKI et al (1996) e BREMMER et al (1997 encontraram aumentos no teor e/ou na produção de proteína pelo leite. Esses autores sugeriram que aumentos nas concentrações plasmáticas de metionina possibilitam acréscimo na concentração de nitrogênio no plasma, devido à maior passagem de aminoácidos para o intestino delgado, sem sofrer degradação microbiana no rúmen, aumentando a disponibilidade na glândula mamária, permitindo aumento na síntese de proteína do leite.…”
Section: Rev Bras Zootec 290unclassified
“…Ardalan et al (2010) reported that the reproductive performance of cows fed methionine hydroxy analog was improved. Dietary supplementation with RPMet in the first 90 days of lactation did not affect the time to first observed oestrus, days to first service, services per conception, calving interval or days of retained placenta and metritis (Rogers et al 1989, Polan 1991, Ardalan et al, 2010. However, the same methionine source increased the days to first conception, services per conception, incidences of cysts and did not affect reproductive cycling of dairy cows (Bobe 1997, Ardalan et al 2010.…”
Section: Introductionmentioning
confidence: 97%